First-in-Men Online Adaptive Robotic Stereotactic Body Radiation Therapy: Toward Ultrahypofractionation for High-Risk Prostate Cancer Patients - Victor J. Brand, MD; Maaike T.W. Milder, PhD; Miranda E.M.C. Christianen, MD, PhD; Kim C. de Vries, MD; Mischa S. Hoogeman, PhD; Luca Incrocci, MD, PhD; Femke E. Froklage, MD, PhD (Advances in Radiation Oncology)
Purpose: Ultrahypofractionation presents challenges for a subset of high-risk prostate cancer patients due to the large planning target volume (PTV) margin required for the seminal vesicles. Online adaptive radiation therapy could potentially reduce this margin. This paper focuses on the development, preclinical validation, and clinical testing of online adaptive robotic stereotactic body radiation therapy for this patient group. Methods and Materials: An online adaptive workflow was developed for the CyberKnife with integrated in-room CT-on-rails. Preclinical validation involved comparing deep learning–based auto-contouring with deformable or rigid contour propagation in terms of subsequent editing time. A fast treatment planning method was implemented and compared with the conventional method in terms of optimization time and adherence to planning constraints. Clinical testing was conducted in the first study patients of the UPRATE trial, which investigates the feasibility of seminal vesicle PTV margin reduction in low-volume metastasized prostate cancer patients. Treatment time and patient experience were recorded. Results: Rigid registration for prostate and deep-learning auto-contouring for seminal vesicles and organs at risk were selected based on editing time and robustness for anatomic changes. The fast treatment planning method reduced the optimization time from 10 to 3.5 minutes (P = .005). No significant differences in dose parameters were observed compared with the conventional plans. During clinical testing, 53 of 60 fast treatment plans adhered to the planning constraints, and all 60 were clinically accepted and delivered. The average total treatment time was 67.7 minutes, showing a downward trend. The treatment was well-experienced overall. Conclusions: Online adaptive stereotactic body radiation therapy using CyberKnife with integrated CT-on-rails is clinically feasible for prostate cancer patients with seminal vesicles included in the target volume. The UPRATE trial outcome will reveal the extent to which online adaptation can reduce the PTV margin of the seminal vesicles.